Structure and Funding of Clinical Informatics Fellowships: A National Survey of Program Directors - Patel, Tushar N.; Chaise, Aaron J.; Hanna, John J.; Patel, Kunal P.; Kochendorfer, Karl M.; Medford, Richard J.; Mize, Dara E.; Melnick, Edward R.; Hron, Jonathan D.; Youens, Kenneth; Pandita, Deepti; Leu, Michael G.; Ator, Gregory A.; Yu, Feliciano; Genes, Nicholas; Baker, Carrie K.; Bell, Douglas S.; Pevnick, Joshua M.; Conrad, Steven A.; Chandawarkar, Aarti R.; Rogers, Kendall M.; Kaelber, David C.; Singh, Ila R.; Levy, Bruce P.; Finnell, John T.; Kannry, Joseph; Pageler, Natalie M.; Mohan, Vishnu; Lehmann, Christoph U. (Applied Clinical Informatics, 2024)
Background In 2011, the American Board of Medical Specialties established clinical informatics (CI) as a subspecialty in medicine, jointly administered by the American Board of Pathology and the American Board of Preventive Medicine. Subsequently, many institutions created CI fellowship training programs to meet the growing need for informaticists. Although many programs share similar features, there is considerable variation in program funding and administrative structures.Objectives The aim of our study was to characterize CI fellowship program features, including governance structures, funding sources, and expenses.Methods We created a cross-sectional online REDCap survey with 44 items requesting information on program administration, fellows, administrative support, funding sources, and expenses. We surveyed program directors of programs accredited by the Accreditation Council for Graduate Medical Education between 2014 and 2021.Results We invited 54 program directors, of which 41 (76%) completed the survey. The average administrative support received was $27,732/year. Most programs (85.4%) were accredited to have two or more fellows per year. Programs were administratively housed under six departments: Internal Medicine (17; 41.5%), Pediatrics (7; 17.1%), Pathology (6; 14.6%), Family Medicine (6; 14.6%), Emergency Medicine (4; 9.8%), and Anesthesiology (1; 2.4%). Funding sources for CI fellowship program directors included: hospital or health systems (28.3%), clinical departments (28.3%), graduate medical education office (13.2%), biomedical informatics department (9.4%), hospital information technology (9.4%), research and grants (7.5%), and other sources (3.8%) that included philanthropy and external entities.Conclusion CI fellowships have been established in leading academic and community health care systems across the country. Due to their unique training requirements, these programs require significant resources for education, administration, and recruitment. There continues to be considerable heterogeneity in funding models between programs. Our survey findings reinforce the need for reformed federal funding models for informatics practice and training.
Keywords: clinical informatics; physician; workforce; ACGME; fellowships and scholarships; internships and residency; medical informatics